2016
DOI: 10.17507/tpls.0605.03
|View full text |Cite
|
Sign up to set email alerts
|

Code Switching in EFL Classrooms: A Bangladeshi Perspective

Abstract: Abstract-Code switching (CS) in classrooms, especially in bilingual classes, is a common phenomenon. This paper tends to expose the plausible reasons behind the application of first language (L1) in English as Foreign Language (EFL) classrooms where English is considered the medium of instruction in all spheres of pedagogical issues. Another important aspect of this study is to reveal the perception of both students and teachers towards their CS to L1. The findings of this survey show that a switch to L1, whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In this study, to support the qualitative data, questionnaires were used as the instrument of this study. The questionnaires were adapted from the questionnaires in Obaidullah (2016). The participants were asked to fill the questionnaires based on their perception.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, to support the qualitative data, questionnaires were used as the instrument of this study. The questionnaires were adapted from the questionnaires in Obaidullah (2016). The participants were asked to fill the questionnaires based on their perception.…”
Section: Methodsmentioning
confidence: 99%
“…On Muin (2011) perspective, SC is used by the speaker as a strategy to communicate with our interlocutor in order to keep a communication run on. Supporting Muin's opinion, Syam et al (2018) claimed that code switching is beneficial for teachers and students to provide explanations about the subject matter to students, to get overall comprehension of conversation (Mahdi & Almalki, 2019), to make students understand difficult and new vocabularies in the text (Obaidullah, 2016), to achieve personal motivations and communicative efficiency (Castillejo, Calizo, & Maguddayao, 2018), and to promote relationship with students, to switch the topic, and to persuade or motivate students to be more engaged in learning English. In addition, Orynbek ( 2020) reported that in the classroom practices, participant do code switching for these reasons; to avoid misunderstanding, to help in comprehending the message delivered, to attract attention, to quote something said by others, to express loyalty to their culture, to create a sense of belonging, to persuade others, to discuss certain topics, to make the lesson more enjoyable, to crack jokes, to express themselves easily, to express personal emotions (e.g.anger, sadness, happiness, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The use of CS quite often happen in EFL practices of teaching and learning over the world in which English is learned formally. It is used unconsciously by teacher or the students during conducting conversation (Wang & Wu, 2016) wrote, the study of classroom code-switching has been frequently studied over a few decade and conducted in many countries, such as in Algeria (Henni, 2017), in Bangladesh (Obaidullah, 2016), in China (Wang & Wu, 2016), in Malaysia (Sardar et al, 2015), (Rahimi & Eftekhari, 2011), in Los Angeles (Lowi, 2005) and in Ethiopia (Sime, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Obaidullah (2016) believes that as a result of codeswitching to first langauge, the topic or subject of discussion in the classroom is more comprehensible regardless of whether the teacher or student had engaged in code-switching. Similarly, Ray (2015) asserted that codeswitching and the use of native language is of great benefit to students even if they relate to higher proficiency classes.…”
mentioning
confidence: 99%
“…Another study by Obaidullah (2016) investigated the reasons for the first language usage in EFL classrooms and to study the perceptions of both teachers and students about code-switching. Survey method was used to collect data from 34 teachers and 175 students from two Bangladeshi universities (Northern University Bangladesh and Kulna University).…”
mentioning
confidence: 99%